2021
DOI: 10.15386/mpr-1842
|View full text |Cite
|
Sign up to set email alerts
|

The importance of androgen receptors in breast cancer

Abstract: Background and aim. Breast cancer (BC) is the most common malignancy among women worldwide, and one of the leading causes of cancer-related deaths in females. For the breast malignant tumors there are numerous targeted therapies, depending on the receptors expressed. Regulating the process of epithelial-mesenchyme transcription, the steroid nuclear receptors are important in invasion and progression of BC cells. Till now, it is known that androgen receptor (AR) is present in about 60-80% of BC cells but, unfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
(83 reference statements)
0
4
0
Order By: Relevance
“…AR is a member of the steroid receptor family, and it is associated with a wide range of tumors, including breast cancer, prostate cancer, and ovarian cancer [ 32 34 ]. Additionally, accumulating evidence showed AR overexpression in EAC; immunohistochemistry studies reported that AR expression was observed in 45–97.4% of cases [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…AR is a member of the steroid receptor family, and it is associated with a wide range of tumors, including breast cancer, prostate cancer, and ovarian cancer [ 32 34 ]. Additionally, accumulating evidence showed AR overexpression in EAC; immunohistochemistry studies reported that AR expression was observed in 45–97.4% of cases [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, three other compounds detected in the ethyl acetate extract of PBR1 strain, viz. Spiro [5.5] undecane, 1-methylene, 9-acridanone, 9-Acridanone, 1-ethoxy-3-methoxy- 10-methyl, and fluoxymesterone detected in the ethyl acetate extract of PBR1 strain, exhibited antimicrobial, antiviral, antimalarial, anti-inflammatory, and antianemia activities [ 45 , 46 , 47 , 48 , 49 ]. Similarly, in Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, experimental evidence indicates that in ERα/β-positive BC, ERα promotes proliferation while ERβ negatively regulates ERα [ 8 ]. In addition, recent data suggest that androgen receptor (AR) expression and activity might play a role in BC progression and, indeed, higher AR/ERα ratio is an independent predictor of disease-free survival [ 9 ].…”
Section: Introductionmentioning
confidence: 99%